Praktik Sewa Lahan Pertanian di Masyarakat Perspektif Hukum Ekonomi Islam - Muhamad Wildan Fawa’id; Nur Huda (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2020)
Indonesia is an agrarian country. About 13% of the total land area in Indonesia is used for agriculture. Then, about 5% of them are located on Java Island, approximately 7.1 million hectares the area of this agricultural land in its management is more managed by the community, with a variety of akad done. Starting from rent for a season, a year even buy. For people who are farmed but do not have farmland, to buy will feel heavy, because the price of land will continue to crawl up from year to year. The solution is the lease. Like a rental in general, tenants only have the right to make use of not selling. But according to some Ahaadeeth rented farmland was not allowed by the prophet. But using the analytical descriptive method of the study replied that the lease of farmland forbidden by the prophet was rent by paying using the harvest. But no one can guarantee this land can be harvested or not. From here comes speculation, whereas in Islam we are forbidden for speculation. So the rental of land is allowed because as long as paying rent using money, not agricultural products. So the element of speculation and harm can be eliminated